Lagochilascaris minor Leiper, 1909 (Nematoda: Ascarididae) in Mexico: three clinical cases from the Peninsula of Yucatan - Barrera-Pérez, Mario; Manrique-Saide, Pablo; Reyes-Novelo, Enrique; Escobedo-Ortegón, Javier; Sánchez-Moreno, Manuel; Sánchez, Cuauhtémoc (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
Human lagochilascariasis (HL) is a parasite produced by Lagochilascaris minor Leiper 1909 that also can be found in cats and dogs. HL is considered an emerging zoonosis in the Americas, spreading from Mexico to Argentina, and the Caribbean Islands. The present paper describes three HL cases from the Peninsula of Yucatan, Mexico, recorded in the last decade. It describes the characteristics of the lesions and discusses the route of transmission in humans and particularly in the observed patients.